Placental characteristics in monochorionic twins with selective intrauterine growth restriction in relation to the umbilical artery Doppler classification. (November 2018) - Groene, S.G.; Tollenaar, L.S.A.; Slaghekke, F.; Middeldorp, J.M.; Haak, M.; Oepkes, D.; Lopriore, E.
Abstract: Introduction: The objective of this study was to evaluate the placental characteristics of monochorionic twin pregnancies with selective intrauterine growth restriction (sIUGR) classified according to the Gratacós classification based on umbilical artery Doppler measurements. Methods: All consecutive placentas from monochorionic twin pregnancies with sIUGR, (defined as a birthweight discordance > 25% and/or an estimated fetal weight in one twin <10th centile) examined between May 2002 and February 2018 were included in the study. Each placenta was injected with colored dye to study the angioarchitecture. Primary outcomes were placental share discordance and diameter of the arterio-arterial anastomoses in relation to the umbilical artery Doppler types of sIUGR (Gratacós classification). Results: Of the 83 sIUGR twins included, 27 were classified as Gratacós type I, 24 as type II and 32 as type III. The median gestational age at delivery was 34.3 weeks for type I, compared to 31.2 weeks and 31.6 weeks for type II and type III respectively. A trend towards a higher placental share discordance in type III sIUGR was observed. The median arterio-arterial diameter was 1.7 mm (0.8–2.6) in type I, 1.7 mm (1.2–2.2) in type II and 2.8 (2.0–3.5) mm in type III (p < 0.01). Discussion: Type III sIUGR placentas appear to be characterized by a larger diameter of the arterio-arterial anastomoses and a larger placental share discordance compared to type I and II sIUGR. The insights in the placental architecture of sIUGR placentas may offer new views on the pathophysiology of the disease. Highlights: Selective intrauterine growth restriction results from unequal placental sharing. Gratacós type III demonstrates the largest arterio-arterial anastomosal diameter. Gratacós type III shows a trend towards the highest placental share discordance.